2021
DOI: 10.7759/cureus.14112
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Risk Assessment and Prediction Tool (RAPT) Score for Primary Hip and Knee Arthroplasty Patients: A Single-Center Study

Abstract: The Risk Assessment and Prediction Tool (RAPT) was developed to predict patient discharge destination for arthroplasty operations. However, since Enhanced Recovery After Surgery (ERAS) programs have been utilized in the UK, the RAPT score has not been validated for use. The aim of the current study was to evaluate the predictive validity of the RAPT score in an ERAS environment with short length of stay. Data were compiled from 545 patients receiving a primary elective total hip or total knee arthroplasty in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Additionally, a lower RAPT score served as a significant predictive factor of an increased LOS; outpatients had the highest averaged RAPT score, and those with prolonged-stay patients had the lowest RAPT (outpatient: 10.0; short stay: 9.0; prolonged stay: 8.2; P < .001), which is consistent with existing studies [ 39 , 40 ]. Also, an unexpected admission or hospital transfer implied by the absence of RAPT was predictive of an increased LOS (outpatient: n = 21, 9.1%; short stay: n = 117, 13.0%; prolonged stay: n = 89, 33.3%; P < .001).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, a lower RAPT score served as a significant predictive factor of an increased LOS; outpatients had the highest averaged RAPT score, and those with prolonged-stay patients had the lowest RAPT (outpatient: 10.0; short stay: 9.0; prolonged stay: 8.2; P < .001), which is consistent with existing studies [ 39 , 40 ]. Also, an unexpected admission or hospital transfer implied by the absence of RAPT was predictive of an increased LOS (outpatient: n = 21, 9.1%; short stay: n = 117, 13.0%; prolonged stay: n = 89, 33.3%; P < .001).…”
Section: Discussionsupporting
confidence: 89%
“…Alshawani et al found RAPT to be somewhat predictive of LOS, but not of discharge destination among a patient population in the United Kingdom. 16 Most recently, Oeding et al 17 found the RAPT score to be associated with inpatient versus outpatient status after TKA and THA. RAPT's ability to predict discharge deserves additional investigation, especially as fewer patients are being discharged to rehab facilities than in the past.…”
Section: Discussionmentioning
confidence: 99%
“…More research has been done in the lower extremity arthroplasty patients. 3,5,6,[27][28][29][30][31][32][33] To date, at least 10 tools have been developed and published to help determine discharge disposition after TJA, but no one tool has been shown to be superior in ease of use and reliability. 27 One of the Graph showing the association between risk score and clinical outcomes among outpatients.…”
Section: Discussionmentioning
confidence: 99%